If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(33 + -3X) + 1X = 27 (33 * 3 + -3X * 3) + 1X = 27 (99 + -9X) + 1X = 27 Combine like terms: -9X + 1X = -8X 99 + -8X = 27 Solving 99 + -8X = 27 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-99' to each side of the equation. 99 + -99 + -8X = 27 + -99 Combine like terms: 99 + -99 = 0 0 + -8X = 27 + -99 -8X = 27 + -99 Combine like terms: 27 + -99 = -72 -8X = -72 Divide each side by '-8'. X = 9 Simplifying X = 9
| 2t^2-5t-25=0 | | 2f(3d+5)= | | 1+2y=-2 | | 5x/10=-25 | | 0.4n=-60 | | 26=8*x/2 | | 6x+1=3k+3 | | 4*1+y=6 | | 4*0+y=6 | | 6t(7-2t)= | | x=20/30x | | 38-9x=17+12x | | 45/x=3 | | 2b+3a=100 | | -(6x+w)+6(4w-4x)= | | -9s+5=-1-5s | | 13x+15y=2 | | x^2+20x+-9=0 | | x-2=3x-91 | | 4. 5c-c+4c-2c= | | sin^2x=1/2 | | 8x+25=2x+187 | | 25x^2-10x+28=0 | | x=8x+25 | | -(-3x^2-3/5x-5) | | (x^4/7)^7 | | 2y-5x+6=0 | | -2=2y+2 | | 5c(2d+E)= | | 5(1)+y=7 | | 5(0)+y=7 | | x=10-62 |